Endourologists vs Urologists: The Impact of Surgical Experience and Annual Case Volume on Percutaneous Nephrolithotomy Outcomes - Sahin, Yusuf; Sahin, Sergen; Yilmaz, Mehmet; Muslumanoglu, Ahmet Yaser (Scripta Medica, 2023)
Background/Aim: Surgeon experience, which is an important factor in reducing surgical complications, has been underestimated when analysing percutaneous nephrolithotomy (PNL) outcomes. Aim of this study was to investigate the impact of annual case volume (ACV) of endourologists and urologists on PNL outcomes including stone-free status (SFS) and complications. Methods: A total of 530 patients who underwent PNL in the Clinic between January 2018 and January 2023 were retrospectively analysed. The patients were divided into two groups: those operated by endourologists (Group 1, n = 324) and by urologists (Group 2, n = 206). The two groups were statistically compared in terms of postoperative SFS and complications. Results: There were two endourologists in Group 1 and four urologists in Group 2. The mean ACV was 73.56 ± 7.43 in Group 1 and 23.81 ± 9.09 in Group 2, indicating a statistically significantly higher rate in Group 1 (p < 0.001). There was no statistically significant difference in the postoperative SFS rates between the groups (p = 0.064). In the perioperative period, the mean estimated blood loss and nephrostomy dwell time were significantly lower in Group 1 than Group 2 (p = 0.013 and p = 0.008, respectively). In the logistic regression analysis, a cut-off value of > 24 for ACV and CROES scores were the significant predictors of SFS (p = 0.004 and p < 0.001, respectively). The complication rate was significantly lower among surgeons with an ACV of > 24 (p < 0.001). Conclusion: Results from this study showed that an ACV of > 24 increases SFS rate by 2.13 with lower complication rates in patients undergoing PNL. Further multi-centre, large-scale studies are required to investigate the effect of surgical experience and ACV on postoperative outcomes and to predict PNL outcomes with high accuracy.